Impact of Debaryomyces hansenii and Saccharomyces cerevisiae cell free extracts on yoghurt quality - Abdullah, Manal M.; Elbarbary, Hend A.; Mohamed, Hamdi A.; Nassif, Marionette Z. (Journal of Advanced Veterinary Research, 2024)
Beneficial yeast extracts mainly of Debaryomyces and Saccharomyces species, have been considered as one of the natural biological fermenters of food products. These yeast metabolites, specially their mycocins can be used to prolong storage time of yoghurt. This study was undertaken to assess the effect of mycocin (Debaryomyces hansenii (DH) and/or Saccharomyces cerevisiae (SC) cell free extracts) (CFEs) on yoghurt quality. Yoghurt samples examined for coagulation time, titratable acidity, sensory and microbiological quality at appropriate intervals until the appearance of spoilage (texture changes). The pre-heated skimmed milk was mixed with starter culture and then it was divided into 10 groups, each inoculated by different inoculum and a certain concentration of (DH) and/or (SC) CFEs (100, 200 and 400 ppm) and incubated at 42oC till curd formation, then refrigerated at 4Â±1oC and examined every 3 day till appearance signs of spoilage. The obtained results revealed a significant elongated coagulation time with the mycocin concentration (400 ppm). During the storage period, titratable acidity steadily rose in all groups. In addition, a significant improvement in the sensory quality parameters represented by flavor, appearance and texture characters appeared with the treated groups with mycocin concentration (100 ppm) compared with the other groups. Regarding to the total fungal count, treated groups with mycocin (400 ppm) showed the most significant inhibitory effect on fungal growth. In conclusion, DH and SC mycocins at concentration of 100 ppm could significantly extend shelf-life of treated yoghurt samples with the highest flavor and texture scores in comparing to the control and the other treated groups.